Empowering Employee Performance Through Competence and Workplace Facilities at PT. Riau Media Televisi (RTV) Pekanbaru - Ergi Bimo Wansyahputra; Okta Karneli (Lembaga Riset dan Inovasi Al-Matani, 2025)
Employee performance plays a crucial role in achieving the long-term success of PT. Riau Media Televisi Pekanbaru in the competitive media industry. Several factors, such as competence and workplace facilities, influence employee performance at PT. Riau Media Televisi Pekanbaru. To ensure continuous improvement in performance, employees must possess strong competencies. This study aims to examine and analyze the influence of competence and workplace facilities on employee performance at PT. Riau Media Televisi Pekanbaru. The research involved 64 respondents, representing the total number of employees at the company. A census or total sampling technique was used for data collection. The study applied various analytical tests, including validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²) test. The results indicate that competence and workplace facilities have a significant and positive effect on employee performance at PT. Riau Media Televisi Pekanbaru.